Comparative study of Newton’s method, Broyden’s method and Steepest Descent method / Nur Alia Syahirah Mazlan and Nurzahida Mohd Zaharuddin - Mazlan, Nur Alia Syahirah; Mohd Zaharuddin, Nurzahida (2019)
Mathematically, numerical analysis is the area of computer science and computer mathematics that creates,analyses and implements for solving of continous mathematics in numerical problem.Thus, this research significantly presents a detailed study of the comparison in iterative methods for solving non-linear system using Newton’s Method, Broyden’s Method and Steepest Descent’s Method.These iterative methods are choose since they are well-known basic iterative methods in numerical analysis.The purpose of this study is to identify which method is the most efficient based on its number of iteration and CPU time.Therefore, researchers can decide the most appropriate method for their work by the comperative study.